2008
DOI: 10.1890/07-0529.1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Adaptive Plasticity: Risk‐sensitive Hatching in Neotropical Leaf‐breeding Treefrogs

Abstract: Abstract. Adaptive plasticity at switch points in complex life cycles (e.g., hatching, metamorphosis) is well known, but the evolutionary history of such plasticity is not. Particularly unclear is how a single plastic response (e.g., shifts in hatching timing) evolves to respond to different threats and cues (e.g., abiotic and biotic). We conducted a comparative phylogenetic study of hatching plasticity in a group of frogs with arboreal embryos to determine when risk-accelerated hatching evolved in the clade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 124 publications
1
120
0
4
Order By: Relevance
“…Particularly at early developmental stages, this is the predominant functional framework for investigations of embryo behavior. Research on adaptive plasticity in hatching has demonstrated that embryo behavior, and appropriate responses to environmental cues, can be also of immediate importance for survival (Warkentin, 2007;Gomez-Mestre et al, 2008;Warkentin and Caldwell, in press). Similarly, behavioral interactions of bird embryos, shortly before hatching, with parents and siblings appear to have immediate functions in care solicitation and hatching synchronization (Brua, 2002).…”
Section: Adaptive Embryo Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly at early developmental stages, this is the predominant functional framework for investigations of embryo behavior. Research on adaptive plasticity in hatching has demonstrated that embryo behavior, and appropriate responses to environmental cues, can be also of immediate importance for survival (Warkentin, 2007;Gomez-Mestre et al, 2008;Warkentin and Caldwell, in press). Similarly, behavioral interactions of bird embryos, shortly before hatching, with parents and siblings appear to have immediate functions in care solicitation and hatching synchronization (Brua, 2002).…”
Section: Adaptive Embryo Behaviormentioning
confidence: 99%
“…While solving a physiological problem, hatching earlier may, however, create an ecological one. More mature hatchlings typically have greater sensory development and/or locomotor abilities (Fuiman, 2002), both of which can reduce mortality from predation (Sih and Moore, 1993;Warkentin, 1999a;Gomez-Mestre et al, 2008). If predators or other factors in the post-hatching environment impose selection for later hatching, then mechanisms to extend embryonic development will be favored (Warkentin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Agalychnis callidryas eggs are laid in masses of, on average, 40 eggs (Gomez-Mestre et al, 2008b) that are attached to a substrate by a layer of jelly. Egg masses on leaves were collected from Ocelot Pond (9°6′8.62″N, 79°40′56.96″W), Bridge Pond (9°6′50.26″N, 79°41′48.13″W) and Experimental Pond (9°7′14.77″N, 79°42′ 12.03″W) near and in Gamboa, Panamá, under permits from the Panamanian Autoridad Nacional del Ambiente (SE/A-41-08, SE/A-13-11, SC/A-19-11 and SC/A-16-12).…”
Section: Materials and Methods Egg Collection And Carementioning
confidence: 99%
“…Other phyllomedusines can also hatch rapidly from their terrestrial eggs (e.g. Agalychnis annae, A. moreletti, Pachymedusa dacnicolor, Cruziohyla calcarifer; Gomez-Mestre et al, 2008b) and may share the rapid hatching mechanism of A. callidryas. Clades that have independently evolved terrestrial eggs and rapid escape-hatching [e.g.…”
Section: Hg Distribution and Functionmentioning
confidence: 99%
See 1 more Smart Citation